The Influence of Digital HR Digitalization on Sustainable Performance through Organizational Learning Capability - Sayugo Adi Purwanto; Siti Munawaroh; Darmono Darmono (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study investigates the nexus between human resource digitalization and sustainable performance, specifically examining how organizational learning capability functions as a vital intermediary. Adopting a quantitative methodology, empirical evidence was gathered from a sample of 300 employees and rigorously analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The empirical results demonstrate that the digital transformation of HR functions exerts a profound and positive influence on both the capacity for organizational learning and the attainment of long-term sustainable performance. The findings suggest that digital HR frameworks do more than just streamline administrative tasks, it cultivates an environment conducive to knowledge acquisition, adaptability, and strategic agility in the face of ecological and market shifts. Furthermore, the analysis identifies organizational learning capability as a significant partial mediator, implying that the impact of digital tools on sustainability is most potent when the organization can effectively translate technological resources into collective wisdom. By bridging digital HRM literature with organizational learning theory, this research offers critical insights for practitioners aiming to harmonize digital investments with a culture of continuous improvement to secure an enduring competitive advantage.